2011
DOI: 10.1007/s12010-011-9239-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Osmotic Stress on Fermentative Production of Succinic Acid by Actinobacillus succinogenes

Abstract: This study investigated the influence of osmotic stress on succinic acid production by Actinobacillus succinogenes NJ113. Both cell growth and succinic acid production were inhibited with the increase in osmotic stress of the medium. The use of three different osmoprotectants in the production of succinic acid was studied in order to decrease the inhibitory effects of osmotic stress during fermentation. Results indicated that proline offers optimal osmoprotection in the production of succinic acid by A. succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Supplementation with betaine increased the cell growth rate, glucose consumption rate, and succinate productivity of engineered E. coli strains in a high initial glucose concentration (150 g/liter) (19). Supplementation with proline increased the succinate titer by 22% from engineered Actinobacillus succinogenes under high osmotic pressure (20). The expression of exogenous betaine biosynthesis genes from the extreme halophile Ectothiorhodospira halochloris resulted in a recombinant E. coli with double the cellular yield compared to that of its control strain in 0.5 M NaCl (21).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation with betaine increased the cell growth rate, glucose consumption rate, and succinate productivity of engineered E. coli strains in a high initial glucose concentration (150 g/liter) (19). Supplementation with proline increased the succinate titer by 22% from engineered Actinobacillus succinogenes under high osmotic pressure (20). The expression of exogenous betaine biosynthesis genes from the extreme halophile Ectothiorhodospira halochloris resulted in a recombinant E. coli with double the cellular yield compared to that of its control strain in 0.5 M NaCl (21).…”
Section: Resultsmentioning
confidence: 99%
“…After challenge at pH 4.0 for 5 H, the survival rate of L. lactis NZ9000 (Leu+) increased 28.5‐fold compared to L. lactis NZ9000 (Leu − ). In addition, the succinic acid production of Actinobacillus succinogenes NJ113 was increased by 22.2% with the addition of 25 mM proline . Furthermore, the addition of 1 mM glycine betaine to the growth medium partially relieved osmotic pressure stress in Desulfovibrio halophilus .…”
Section: Process Engineering To Improve Microbial Stress Resistancementioning
confidence: 97%
“…Compatible solutes are usually impermeable to the cell membrane, less toxic at high internal concentrations, and not easily catabolized [ 6 , 8 ], which greatly facilitates water remaining within the cytoplasm. In terms of SA production, it was reported that medium supplemented with glycine-betaine or proline improved cell osmotolerance and succinate production in E. coli [ 12 ] and Actinobacillus succinogenes [ 13 ]. However, it is worth noting that the osmoprotective effects of these compatible solutes are conditional.…”
Section: Introductionmentioning
confidence: 99%